2021
DOI: 10.1002/ijc.33596
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the oral and gut microbiome of colorectal cancer patients and association with host clinical factors

Abstract: Previous studies have suggested that gut microbiota plays a critical role in colorectal cancer (CRC). Although preliminary comparisons of the oral and gut microbiota between CRC and healthy control (HC) patients have been made, the association between microbiome abundance and host clinical factors has not been fully illustrated, especially oral health conditions. Matching samples of unstimulated saliva, cancer tissues or biopsies and stools were collected from 30 CRC and 30 HC patients from Shanghai Jiao Tong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 46 publications
2
28
3
Order By: Relevance
“…However, our findings showed that F. nucleatum may or may not be derived from the oral cavity, depending on the subspecies and strain, and some may or may not affect CRC progression. Furthermore, oral hygiene tended to be worse in patients with CRC compared to that in controls in previous studies [23][24][25]. Similarly, we found poor oral hygiene in our cohort of patients with CRC.…”
Section: Discussionsupporting
confidence: 78%
“…However, our findings showed that F. nucleatum may or may not be derived from the oral cavity, depending on the subspecies and strain, and some may or may not affect CRC progression. Furthermore, oral hygiene tended to be worse in patients with CRC compared to that in controls in previous studies [23][24][25]. Similarly, we found poor oral hygiene in our cohort of patients with CRC.…”
Section: Discussionsupporting
confidence: 78%
“…After assessing the full text of 112 studies, 73 studies were additionally excluded as not meeting the requirements: 19 evaluated only fecal microbiota; 14 did not include controls; 13 used 16S rRNA data from previously published studies; 10 had another outcome or study design; five analyzed specific bacterial species, four did not have CRC cases; four used colonoscopy aspirates or tissue swabs; two did not characterize the microbiota; and two presented animal data only. A total of 39 studies were included in the present systematic review [ 19 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. The PRISMA flow-chart of the study inclusion process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The tissue microbiota composition of CRC was compared with that of healthy controls in six studies [ 33 , 34 , 35 , 36 , 68 , 69 ] ( Table 1 ) and with that of non-cancerous colon tissue of CRC patients in 27 studies ( Table 2 ) [ 19 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 62 , 63 , 64 , 66 , 67 , 70 ]. Six studies included both comparisons [ 57 , 58 , 59 , 60 , 61 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, strains harboring the pks genomic island (pks + E. coli ) produce colibactin, which is subject of research in relation to CC during the last decade ( Faïs et al, 2018 ). Microbiome studies aiming at the identification of bacterial genera and abundance of bacterial species in the gut of CRC patients revealed a significantly reduced (relative) abundance of Escherichia in feces of CRC patients compared to healthy controls ( Sheng et al, 2019 ; Tang et al, 2020 ; Wang Y. et al, 2021 ). Supplementary Table 9 summarizes the results of 14 studies assessing the link between (mainly) oncogenic/cyclomodulin-producing E. coli and CRC ( Buc et al, 2013 ; Bonnet et al, 2014 ; Kohoutova et al, 2014 ; Fukugaiti et al, 2015 ; Xie et al, 2016 ; Shimpoh et al, 2017 ; Tsuchiya et al, 2018 ; Tunsjø et al, 2019 ; Zarei et al, 2019 ; Iyadorai et al, 2020 ; Pleguezuelos-Manzano et al, 2020 ; Rezasoltani et al, 2020 ; Tang et al, 2020 ; Yoshikawa et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%